2024
DOI: 10.1038/s44321-023-00008-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and safe therapeutic use of paired Cas9-nickases for primary hyperoxaluria type 1

Laura Torella,
Julia Klermund,
Martin Bilbao-Arribas
et al.

Abstract: The therapeutic use of adeno-associated viral vector (AAV)-mediated gene disruption using CRISPR-Cas9 is limited by potential off-target modifications and the risk of uncontrolled integration of vector genomes into CRISPR-mediated double-strand breaks. To address these concerns, we explored the use of AAV-delivered paired Staphylococcus aureus nickases (D10ASaCas9) to target the Hao1 gene for the treatment of primary hyperoxaluria type 1 (PH1). Our study demonstrated effective Hao1 gene disruption, a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…However, off-target indels were not systematically evaluated. In a different approach to minimizing off-target effects, a paired-D10ASaCas9n strategy was delivered with the same two sgRNAs by two AAV8 to disrupt Hao1 in the same mouse model [139]. The authors reported 57% editing efficiency in Hao1 (Table 4) and a lower AAV integration rate compared to Cas9 nuclease, resulting in reduced GO protein expression and decreased oxalate accumulation in PH1 mice.…”
Section: Alpha-1 Antitrypsin Deficiencymentioning
confidence: 99%
“…However, off-target indels were not systematically evaluated. In a different approach to minimizing off-target effects, a paired-D10ASaCas9n strategy was delivered with the same two sgRNAs by two AAV8 to disrupt Hao1 in the same mouse model [139]. The authors reported 57% editing efficiency in Hao1 (Table 4) and a lower AAV integration rate compared to Cas9 nuclease, resulting in reduced GO protein expression and decreased oxalate accumulation in PH1 mice.…”
Section: Alpha-1 Antitrypsin Deficiencymentioning
confidence: 99%